Making Foucault coach: turning post-structural assumptions into coaching praxis. Issue 2 (4th May 2022) - Mills, Joseph P.; Gearity, Brian; Kuklick, Clayton; Bible, Jordan
ABSTRACT: Foucauldian-inspired coaching practices have been a recent focus in the Foucauldian coaching studies literature. There can be no denying the emergence of a number of ethical coaching practices in synergy with Foucault's work, yet in most coaches' everyday practices there appears to have been little uptake. Accordingly, our central concern in this paper is considering how Foucault's work could become a more deliberate feature of coaching. Using Thomas Kuhn's concept of paradigms, we argue that more significant change is yet to occur because coach education does not include the post-structural paradigmatic assumptions underpinning Foucault's work. As a result, coaches immersed in a modern disciplinary logic may interpret Foucauldian-inspired practices through incommensurable assumptions. In this paper, we develop numerous post-structural assumptions into coaching post-structural praxis (CPSP) to demonstrate what those assumptions mean for coaches' knowledge and practice.